2023
DOI: 10.1021/acsabm.2c01089
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable Fibrillar Gauze Dressing Based on N-Carboxyethyl Chitosan Gelling Fibers for Fatal Hemorrhage Control

Abstract: Death from lethal hemorrhage remains a major problem in various emergency scenarios. There is a continuous interest in the development of absorbable hemostatic dressings that can control hemorrhage rapidly and can be left in the wound site without removal. In this study, we report a hemostatic gauze dressing based on N-carboxyethyl chitosan (CECS) gelling fibers. The CECS fibrillar gauze combines ultra-hydrophilic, cationic chemical property of the fiber components with the fluffy nonwoven material form, exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Specifically, the CECS-D group presented the shortest hemostasis time (156 ± 43 s) and the lowest blood loss (0.67 ± 0.37 g), which was ∼1/2 fold and ∼1/4 fold of that in the CECS group (328 ± 66 and 2.79 ± 0.81 s) and ∼1/3 fold and ∼1/6 fold of that in the gauze group (464 ± 59 s and 3.81 ± 0.59 g), respectively (Figure C,D). The above results suggest that CECS-D mats present superior hemostatic performance over CECS mats which have been reported to have the same hemostatic effect as commercialized Celox products in a swine femoral artery injury model . Although there was no obvious significant difference between the CECS-D group and CECS group, they showed a hemostasis time of 188 ± 67 and 296 ± 155 s and blood loss of 1.98 ± 0.52 and 3.42 ± 1.91 g for the CECS-D group and CECS group, respectively, which was far lower than that of the gauze group (968 ± 244 s, p < 0.001; 12.14 ± 5.34 g, p < 0.01), revealing high hemostatic efficacy of the CECS-D group and CECS group in rabbit spleen hemorrhage models (Figure E,F).…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Specifically, the CECS-D group presented the shortest hemostasis time (156 ± 43 s) and the lowest blood loss (0.67 ± 0.37 g), which was ∼1/2 fold and ∼1/4 fold of that in the CECS group (328 ± 66 and 2.79 ± 0.81 s) and ∼1/3 fold and ∼1/6 fold of that in the gauze group (464 ± 59 s and 3.81 ± 0.59 g), respectively (Figure C,D). The above results suggest that CECS-D mats present superior hemostatic performance over CECS mats which have been reported to have the same hemostatic effect as commercialized Celox products in a swine femoral artery injury model . Although there was no obvious significant difference between the CECS-D group and CECS group, they showed a hemostasis time of 188 ± 67 and 296 ± 155 s and blood loss of 1.98 ± 0.52 and 3.42 ± 1.91 g for the CECS-D group and CECS group, respectively, which was far lower than that of the gauze group (968 ± 244 s, p < 0.001; 12.14 ± 5.34 g, p < 0.01), revealing high hemostatic efficacy of the CECS-D group and CECS group in rabbit spleen hemorrhage models (Figure E,F).…”
Section: Resultsmentioning
confidence: 64%
“…The above results suggest that CECS-D mats present superior hemostatic performance over CECS mats which have been reported to have the same hemostatic effect as commercialized Celox products in a swine femoral artery injury model. 35 Although there was no obvious significant difference between the CECS-D group and CECS group, they showed a hemostasis time of 188 ± 67 and 296 ± 155 s and blood loss of 1.98 ± 0.52 and 3.42 ± 1.91 g for the CECS-D group and CECS group, respectively, which was far lower than that of the gauze group (968 ± 244 s, p < 0.001; 12.14 ± 5.34 g, p < 0.01), revealing high hemostatic efficacy of the CECS-D group and CECS group in rabbit spleen hemorrhage models (Figure 4E,F). The above results indicated that CECS-D mats had excellent hemostatic capacity.…”
Section: In Vivo Hemostatic Evaluation Of Cecs-d Matsmentioning
confidence: 99%
See 3 more Smart Citations